2019
DOI: 10.1587/nolta.10.337
|View full text |Cite
|
Sign up to set email alerts
|

Delay effects on the limit cycling behavior in resonant inverters with state feedback

Abstract: Bifurcations of limit cycles in an H-bridge LC resonant inverter are reexamined taking into account a time delay in the switching transition. The analysis is accomplished by means of a model of the inverter that compresses, in only three parameters, all the elements associated to both series and parallel topologies of the inverter, to the parasitic effects, to the state feedback control, and to the switching time delay. Emphasis is made in the deviation of preexisting bifurcations without delay and the new one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This situation was also considered in Ref. [6] in an investigation of switch-mode power converters. Using numerical case studies, the authors found periodic orbits as well as smooth and discontinuity induced bifurcations similar to our results.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…This situation was also considered in Ref. [6] in an investigation of switch-mode power converters. Using numerical case studies, the authors found periodic orbits as well as smooth and discontinuity induced bifurcations similar to our results.…”
Section: Introductionmentioning
confidence: 92%
“…In the latter case, trajectories are guaranteed to cross the switching manifold such that solutions of DDE (6) are necessarily oscillatory. In the former case, there are initial conditions that result in nonoscillatory solutions to DDE (6), ones that approach the fixed point without ever crossing the switching manifold. In this paper, we focus on oscillatory solutions and will exclude such initial conditions from consideration.…”
Section: Sample Solutions and Symbolic Representationmentioning
confidence: 99%
See 3 more Smart Citations